Molecular mapping of stem and leaf rust resistance in wheat - Khan, R. R.; Bariana, Harbans S.; Dholakia, Bhushan B.; Naik, S. V.; Lagu, Meena D.; Rathjen, A. J.; Bhavani, Sridhar; Gupta, V. S. (Theoretical and Applied Genetics, 2005)
Stem rust caused by Puccinia graminis f. sp. tritici Eriks and Henn and leaf rust caused by Puccinia triticina Rob. ex Desm. are major constraints to wheat production worldwide. In the present study, F-4-derived SSD population, developed from a cross between Australian cultivars `Schomburgk' and `Yarralinka', was used to identify molecular markers linked to rust resistance genes Lr3a and Sr22. A total of 1,330 RAPD and 100 ISSR primers and 33 SSR primer pairs selected on the basis of chromosomal locations of these genes were used. The ISSR marker UBC 840(540) was found to be linked with Lr3a in repulsion at a distance of 6.0 cM. Markers cfa2019 and cfa2123 flanked Sr22 at a distance of 5.9 cM (distal) and 6.0 cM (proximal), respectively. The use of these markers in combination would predict the presence or absence of Sr22 in breeding populations. A previously identified PCR-based diagnostic marker STS638 linked to Lr20 was validated in this population. This marker showed a recombination value of 7.1 cM with Lr20.

Molecular genetic mapping of quantitative trait loci associated with loaf volume in hexaploid wheat (Triticum aestivum) - Elangovan, M.; Rai, R.; Dholakia, Bhushan B.; Lagu, Meena D.; Tiwari, R.; Gupta, R. K.; Rao, V. S.; Roeder, M. S.; Gupta, V. S. (Journal of Cereal Science, 2008)
Major efforts in wheat research are being made to improve the yield and quality of wheat. Loaf volume (Lv) is the main quality parameter deciding the bread making potential of wheat. To genetically dissect quantitative trait loci (QTLs) for Lv, a Recombinant Inbred Line (RIL) population (F-8) was developed from a cross between two Indian wheat varieties ``H 1977'' and ``HD 2329''. A total of 914 SSR and 100 ISSR primers were used for molecular analysis and the genetic map comprising 19 chromosomes was constructed with 202 SSR markers and 2 HMW glutenin subunit loci: Glu-B1 and Glu-B1. The phenotypic data were collected from six environments including three different agro-climatic zones for 2 consecutive years. Dissection of Lv through AMMI model revealed significant G x E variance for the trait. QTL analysis was performed using composite interval mapping. A total of 30 QTLs for Lv were detected and significant QTLs were identified on 6B and 6D chromosomes; 1B, 1D, 2A, 3A, 513 and 5D also contributed genetically to Lv. Association between 6B and 6D QTLs and variable expression of gliadins on group 6 chromosomes were discussed. QTLs detected in this study were compared with other QTL analysis in wheat. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: breadmaking; loaf volume; QTL; SSR; wheat quality

Molecular mapping of wilt resistance genes in chickpea - Gowda, S. J. M.; Radhika, P.; Kadoo, Narendra Y.; Mhase, L. B.; Gupta, V. S. (Molecular Breeding, 2009)
Fusarium wilt is a widespread and serious chickpea disease caused by the soil-borne fungus Fusarium oxysporum f.sp. ciceri (Foc). We evaluated an F(9) recombinant inbred line population of chickpea for resistance to three Foc races (1, 2 and 3) in pot culture experiments and identified flanking and tightly linked DNA markers for the resistance genes. The simple sequence repeat markers H3A12 and TA110 flanked the Foc1 locus at 3.9 and 2.1 cM, respectively, while Foc2 was mapped 0.2 cM from TA96 and 2.7 cM from H3A12. The H1B06y and TA194 markers flanked the Foc3 locus at 0.2 and 0.7 cM, respectively. These markers were also validated using 16 diverse chickpea genotypes. Identification of tightly linked flanking markers for wilt resistance genes will be useful for their exploitation in breeding programs and to understand the mechanism of resistance and evolution of the genes.
Keywords: fusarium oxysporum; Fusarium wilt; Genetic mapping; Marker validation; Pathogen races

Mapping of QTLs governing agronomic and yield traits in chickpea - Gowda, S. J. M.; Radhika, P.; Mhase, L. B.; Jamadagni, B. M.; Gupta, V. S.; Kadoo, Narendra Y. (Journal of Applied Genetics, 2011)
Chickpea is one of the most important leguminous cool season food crops, cultivated prevalently in South Asia and Middle East. The main objective of this study was to identify quantitative trait loci (QTLs) associated with seven agronomic and yield traits in two recombinant inbred line populations of chickpea derived from the crosses JG62xVijay (JV population) and VijayxICC4958 (VI population) from at least three environments. Single locus QTL analysis involved composite interval mapping (CIM) for individual traits and multiple-trait composite interval mapping (MCIM) for correlated traits to detect pleiotropic QTLs. Two-locus analysis was conducted to identify the main effect QTLs (M-QTLs), epistatic QTLs (E-QTLs) and QTL x environment interactions. Through CIM analysis, a total of 106 significant QTLs (41 in JV and 65 in VI populations) were identified for the seven traits, of which one QTL each for plant height and days to maturity was common in both the populations. Six pleiotropic QTLs that were consistent over the environments were also identified. LG2 in JV and LG1a in VI contained at least one QTL for each trait. Hence, concentrating on these LGs in molecular breeding programs is most likely to bring simultaneous improvement in these traits.
Keywords: Cicer arietinum; QTL analysis; QTL x environment interaction; Two-locus analysis; Yield traits

Molecular mapping of leaf rust resistance gene Lr15 in hexaploid wheat - Dholakia, Bhushan B.; Rajwade, A. V.; Hosmani, P.; Khan, R. R.; Chavan, S.; Reddy, D. M. R.; Lagu, Meena D.; Bansal, Urmil K.; Saini, R. G.; Gupta, V. S. (Molecular Breeding, 2013)
Leaf rust is a widespread and commonly occurring rust disease of wheat. Genetic resistance is the most economical method of reducing losses due to leaf rust. Lr15 has been shown to be present on wheat chromosome 2D and is reported to be a seedling resistance gene. However, tightly linked markers associated with Lr15 have not been reported to date. To identify molecular markers linked to Lr15, an F-2 mapping population of Thatcher x Thatcher-Lr15 was generated. Available wheat simple sequence repeat markers were utilized in parental screening and polymorphic markers were used to analyze the entire population of 221 plants. Phenotypic evaluations of the F-2-derived F-3 progenies with Puccinia triticina Eriks. pathotype 162A (93R15) confirmed the monogenic inheritance of Lr15. The linkage group representing chromosome 2DS was constructed at LOD 4.0 which revealed the closest flanking markers Xgwm4562 and Xgwm102 at a distance of 3.1 and 9.3 cM, respectively. Furthermore, utilization of these flanking markers in combination has successfully identified wheat lines with or without Lr15. These markers could potentially be useful in gene pyramiding with other genes to enhance rust resistance in wheat.
Keywords: Disease resistance; Leaf rust; Marker-assisted selection; Simple sequence repeat; Wheat